Complications of transoral endonasal-controlled combined endoscopic adenoidectomy - Engin Muz, Sami; Huntürk Atilla, Mahmut (ENT Updates, 2020)
Objective: The purpose of this study was to observe and evaluate the possible complications of Transoral Endonasal-Controlled Combined Endoscopic Adenoidectomy (TECCA) as a subtype of power-assisted endoscopic adenoidectomy (PAEA) in pediatric patients. Methods: Sixty-seven children aged between 2 and 12 years who had been diagnosed with adenoid hypertrophy and underwent TECCA from April 2013 to December 2016 as a single procedure (without myringotomy or any kind of tonsil surgery at the same time) were included. Preoperative risk assessment results and intraoperative and post-operative complications were evaluated. Results: Intraoperative and early post-operative bleeding was observed in four (5.97%) patients. There was no post-operative complication except for bleeding and no patients were found to have residual adenoid tissue during the six-month post-operative follow-up period. Conclusion: Endonasal endoscopic control during adenoidectomy helps to identify vascular structures that would normally be at risk of being injured with blind resection. Endoscopic viewing also enables complete removal of intranasal adenoid tissue without significant prolongation in operation time.